Apigenin Prevents Acetaminophen-Induced Liver Injury by Activating the SIRT1 Pathway - Zhao, Licong; Zhang, Jiaqi; Hu, Cheng; Wang, Tao; Lu, Juan; Wu, Chenqu; Chen, Long; Jin, Mingming; Ji, Guang; Cao, Qin; Jiang, Yuanye (Frontiers in Pharmacology, 2020)
Acetaminophen (APAP) overdose is the main cause of acute liver failure. Apigenin (API) is a natural dietary flavonol with high antioxidant capacity. Herein, we investigated protection by API against APAP-induced liver injury in mice, and explored the potential mechanism. Cell viability assays and mice were used to evaluate the effects of API against APAP-induced liver injury. Western blotting, immunofluorescence staining, RT-PCR and Transmission Electron Microscope were carried out to determine the signalling pathways affected by API. Analysis of mouse serum levels of alanine/aspartate aminotransferase (ALT/AST), malondialdehyde (MDA), liver myeloperoxidase (MPO) activity, glutathione (GSH) and reactive oxygen species (ROS) revealed that API (80 mg/kg) owned protective effect on APAP-induced liver injury. Meanwhile, API ameliorated the decreased cell viability in L-02 cells incubated by APAP with a dose dependent. Furthermore, API promoted SIRT1 expression and deacetylated p53. Western blotting showed that API promoted APAP-induced autophagy, activated the NRF2 pathway, and inhibited the transcriptional activation of nuclear p53 in the presence of APAP. Furthermore, SIRT1 inhibitor EX-527 reduced protection by API against APAP-induced hepatotoxicity. Molecular docking results indicate potential interaction between API and SIRT1. API prevents APAP-induced liver injury by regulating the SIRT1-p53 axis, thereby promoting APAP-induced autophagy and ameliorating APAP-induced inflammatory responses and oxidative stress injury.